FORMULASI SKOR KOMPOSIT DALAM MENINGKATKAN KEBERHASILAN PADA MATA PELAJARAN MATEMATIKA - SITI NURCHAYATI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2013)
This study is aimed to determine whether the composite score of standard deviation model gives more possibility for the students to pass on the Mathematics exams rather than that the composite score of empiric model which has been used in the schools previously.The research was conducted in one of Secondary Schools in Bekasi District with 143 students as respondents for each component of the undertaken assess-ment, namely: Daily Test, Mid Semester Test, and Final Semester Test. The assortment of the daily test data was done by taking the whole scores taken in one semester during the learning process, while the data of the Mid Semester Test and Final Semester Test were obtained by providing sets of Mathematics tests with 40 items each. The data taken from the three test, then, was used to calculate the composite score by using the standard deviation model (standard deviation formula) and two empirical models (The formula 3:1:1 and formula 2:1:1). The results ofresearch areas follow: (1) the proportion of students who could complete the whole Mathematics lessons in which their composite score was calculated by using the standard deviation formula is more than those whose composite score was calculated by using formula 3:1:1, (2) the proportion of students who could complete the whole Mathematics lessons in which their composite score was calculated by using the standard deviation formula is more than those whose composite score was calculated by using formula 2:1:1, and (3) the proportion of students who could complete the whole Mathematics lessons in which their composite score was calculated by using the formula 3:1:1 is more than those whose composite score was calculated by using formula 2:1:1. The implication of this study is that the calculation ofthe composite score by using the standard deviation can become the alternative for the calculation of the composite score in schools by keeping the homogeneity of data taken from the daily assessment for Mathematics specifically and other subjects in general.